GAMBARAN ANGKA LEMPENG TOTAL BAKTERI PADA BEDAK USIA 12 BULAN SETELAH DIGUNAKAN - Mayuri, Nindya Sekar; Yusuf, Nabila Islami; Mareta Hera Siswana, Dwi Risyani; Tantiani, Aisyah Putri; Hafid, Naila Akfalia (Jurnal Inkofar, 2025)
The high number of powder users and the side effects caused by using powder that contains bacteria, then research is needed related to the Total Plate Count of bacteria in powder aged 12 months after use. The research method used in this study is an experimental method. The powder sample used was 12 months old after the powder was used without using a particular brand. The results of the calculation of the number of bacterial colonies showed that the sample with the highest number of colonies was sample S as much as 7.9 x 10^3 cfu/gram then sample W as much as 5.5 x 10^2 cfu/gram and sample L as much as <3.0 x 10^2 cfu/gram. As for the WB sample, there was no bacterial growth the same as the control, namely <1.0 x 10^1 cfu/gram. The color of the bacterial colonies that were successfully isolated was mostly white and 1 colony was clear. While for the shape of the colony consists of Spindle, Irregular, Punctiform, Circular. For the elevation of all bacterial colonies is Convex with margins consisting of Entire and Endulate.